การขึ้นรูปชิ้นงานสามมิติโดยใช้เครื่องพิมพ์หยดหมึกตามประสงค์ที่ติดตั้งหัวพิมพ์แบบนิวแมติกส์ - กุญชร สารวงษ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The commercial three-dimensional printers have been successfully employed in many organizations. However, high cost of ownership and maintenance is still prevented them to be adopted in small and medium enterprises. We present our ongoing development of 3D printer system based on drop-on-demand technology that is capable to fabricate three-dimensional objects from photo-curable polymer. The pneumatic-based print-head is our key device to dispense a droplet with reasonable size and repeatability. The polymer inks is specially formulated to used. We find parameter to fabricate square area about 15 X 15 millimeters. The effect of key fabrication parameters will be investigated. The suitable setting of those parameters will be derived to achieve fast speed and accuracy of the square area object printing.